Partial ulnar ostectomy, stereotactic body radiation therapy, and palliative radiation therapy as local limb sparing treatment modalities for ulnar tumors in dogs - Griffin, Maureen A.; Martin, Tiffany Wormhoudt; Thamm, Douglas H.; Worley, Deanna R. (Frontiers in Veterinary Science, 2023)
Background: Information on dogs that undergo limb preserving local treatment for ulnar tumors is currently limited. Objective: To describe the clinical characteristics and outcomes in dogs that underwent partial ulnectomy or radiation therapy (RT) for ulnar bone tumors, and to evaluate potential risk factors for outcomes as well as pre-treatment factors for association with treatment modality selected. Animals: Forty client-owned dogs that underwent partial ulnectomy or RT for an ulnar tumor from July 2006 to July 2021. Methods: The medical records database from a single institution were retrospectively reviewed, and data were recorded and analyzed. Results: Radiation therapy was performed in 24 dogs, with 12 stereotactic body RT (SBRT) and 12 palliative RT (PRT) plans, and partial ulnectomy was performed in 16 dogs. Biomechanical complications occurred in 6/12 (50%) dogs that underwent SBRT, 6/12 dogs that underwent PRT, and 3/16 (18.8%) dogs that underwent ulnectomy. The majority of dogs had a good functional outcome following partial ulnectomy, and no dogs required surgical stabilization of the carpus even with lateral styloid process excision. Pathologic fracture occurred in 4/12 (33.3%) dogs following SBRT and 5/12 (41.7%) dogs following PRT. Local progression or recurrence was documented in 5/12 (41.7%) dogs that underwent SBRT, 2/12 (16.7%) dogs that underwent PRT, and 2/16 (12.5%) dogs that underwent ulnectomy. The overall median survival time was 198 days, and factors that were significantly associated with improved survival time included adjuvant chemotherapy administration and partial ulnectomy as local treatment method for dogs that received chemotherapy. Clinical Relevance: Both RT and ulnectomy were effective and well tolerated local treatment modalities for dogs with ulnar tumors.